2018
DOI: 10.4049/jimmunol.1700967
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Atypical Chemokine Receptor ACKR4 Identifies a Novel Population of Intestinal Submucosal Fibroblasts That Preferentially Expresses Endothelial Cell Regulators

Abstract: Atypical chemokine receptors (ACKRs) are expressed by discrete populations of stromal cells at specific anatomical locations where they control leukocyte migration by scavenging or transporting chemokines. ACKR4 is an atypical receptor for CCL19, CCL21, and CCL25. In skin, ACKR4 plays indispensable roles in regulating CCR7-dependent APC migration, and there is a paucity of migratory APCs in the skin-draining lymph nodes of -deficient mice under steady-state and inflammatory conditions. This is caused by loss o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 63 publications
9
29
0
Order By: Relevance
“…Gapdh , forward: 5′‐GTGCCAGCCTCGTCCCGTAG‐3′, reverse: 5′‐TTGCCGTGAGTGGAGTCATAC‐3′; Abhd14b , forward: 5′‐GCTGCATGGTATCCGCTTCT‐3′, reverse: 5′‐ CAGCTCCAAGGTATCCACCAC‐3′; Acad11 , forward: 5′‐AAGGAAATAGCCAAAGCAGAG‐3′, reverse: 5′‐TAGCCGAACACCGACAAAG‐3′; A ckr4 , forward: 5′‐CAGACGGCACCTCTCCCAGC‐3′, reverse: 5′‐GCAGGAAGACTTTTGCGAACTG‐3′; Il6 , forward: 5′‐TTCCATCCAGTTGCCTTCTT‐3′, reverse: 5′‐ATTTCCACGATTTCCCAGAG‐3′; Mns1 , forward: 5′‐TGAAAGCCGCCTACATGAACA‐3′, reverse: 5′‐AGCAGCCTATCGTGCTCCT‐3′; Mst1 , forward: 5′‐ATTATGTGCGGACCTGCATTATG‐3′, reverse: 5′‐TCCCCATCAGGGTTCCTACAG‐3′; Sema3b , forward: 5′‐TGTCCGAACCTTCAGGCTG‐3′, 5′‐CCCTGCCCAGTTGCATTCTT‐3′; and Tex9 , forward: 5′‐AGGTGGTTCCAGTTCGAGAGA‐3′, reverse: 5′‐GGAGAAGTCTGAGAAATCGTCTG‐3′.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gapdh , forward: 5′‐GTGCCAGCCTCGTCCCGTAG‐3′, reverse: 5′‐TTGCCGTGAGTGGAGTCATAC‐3′; Abhd14b , forward: 5′‐GCTGCATGGTATCCGCTTCT‐3′, reverse: 5′‐ CAGCTCCAAGGTATCCACCAC‐3′; Acad11 , forward: 5′‐AAGGAAATAGCCAAAGCAGAG‐3′, reverse: 5′‐TAGCCGAACACCGACAAAG‐3′; A ckr4 , forward: 5′‐CAGACGGCACCTCTCCCAGC‐3′, reverse: 5′‐GCAGGAAGACTTTTGCGAACTG‐3′; Il6 , forward: 5′‐TTCCATCCAGTTGCCTTCTT‐3′, reverse: 5′‐ATTTCCACGATTTCCCAGAG‐3′; Mns1 , forward: 5′‐TGAAAGCCGCCTACATGAACA‐3′, reverse: 5′‐AGCAGCCTATCGTGCTCCT‐3′; Mst1 , forward: 5′‐ATTATGTGCGGACCTGCATTATG‐3′, reverse: 5′‐TCCCCATCAGGGTTCCTACAG‐3′; Sema3b , forward: 5′‐TGTCCGAACCTTCAGGCTG‐3′, 5′‐CCCTGCCCAGTTGCATTCTT‐3′; and Tex9 , forward: 5′‐AGGTGGTTCCAGTTCGAGAGA‐3′, reverse: 5′‐GGAGAAGTCTGAGAAATCGTCTG‐3′.…”
Section: Methodsmentioning
confidence: 99%
“…In vivo, ACKR4 regulates CCL19 and CCL21 bioavailability in lymphoid and nonlymphoid tissues and thereby supports the directional migration of antigen‐loaded dendritic cells and subsequent manifestation of efficient T cell responses . Until recently, ACKR4 expression was commonly reported on nonhematopoietic cells of various organs, and lately germinal center (GC) B cells were described to be the only lymphocyte subpopulation expressing the receptor . The authors of that study postulate that expression of ACKR4 on GC B cells restricts humoral immune responses by regulating the localization of activated B cells in a B cell‐intrinsic manner.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, IMSC expressing SOX6, CD142 and Wnt pathway genes appear to localize to intestinal crypts and can support epithelial stem cell function(Kinchen et al, 2018), while a population of GLI1-expressing IMSC localized in the pericrypt area has also been shown to mediate colonic stem cell renewal in a murine model (Degirmenci et al, 2018). Similarly two separate populations of fibroblast-like stromal cells (expressing Ackr4 + /CD34 + or Foxl1 + /F3 + ) in the pericrypt region have been reported to drive stem cell proliferation and gut organoid growth in vitro , likely via production of ligands/agonists of the Wnt and BMP pathways (Aoki et al, 2016; Shoshkes-Carmel et al, 2018; Stzepourginski et al, 2017; Thomson et al, 2018). However, it is currently unclear to what extent these different IMSC populations exert redundant functions or play different roles in gut tissue health and disease states.…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have now suggested that CD90 + IMSC may be crucial regulators of gut homeostasis (Huynh et al, 2016; Karpus et al, 2019; Kinchen et al, 2018; Powell et al, 2011; Roulis et al, 2014). However, recent efforts to understand the heterogeneity and function of ISMC using single-cell RNA sequencing (scRNA-seq) and lineage tracing techniques have revealed the existence of multiple functionally distinct subsets (Kinchen et al, 2018; Nanki et al, 2018), many of which produce soluble factors and cytokines likely capable of modulating gut homeostasis and epithelial integrity (Han et al, 2018; Kinchen et al, 2018; Shoshkes-Carmel et al, 2018; Thomson et al, 2018). In particular, IMSC expressing SOX6, CD142 and Wnt pathway genes appear to localize to intestinal crypts and can support epithelial stem cell function(Kinchen et al, 2018), while a population of GLI1-expressing IMSC localized in the pericrypt area has also been shown to mediate colonic stem cell renewal in a murine model (Degirmenci et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…S2F). These bundles of collagen fibers are formed by a layer of fibroblasts only a few cells thick, which have recently been described as Ackr4+ submucosal fibroblasts and also shown to express key endothelial regulators (Thomson et al, 2018).…”
mentioning
confidence: 99%